College preparatory mathematics 1 : Algebra 1 : vol. 2: units 7-12. - Scott Holm;Elaine Kasimatis;Bob Peterson (California : CPM Educational Program, 1994)
To begin with, the course is built around problems. You will spend much of your time discussing problems in groups and less time listening to your teacher tell you rules.
Unit7. The amusement park -- Unit8. The lunch bunch -- Unit9. The buckled railroad truck -- Unit10. The grazing goat: Area and sub problem -- Unit11. The return of a burning candle -- Unit12. The election poster .
Includes index.
Keywords: MATHEMATICS